Do Free Nutritious Meal Programs and Student Well-being Improve Students' Learning Outcomes? Evidence from the Mediating Role of Learning Motivation - Henry Tamboto; Listriyanti Palangda; Jety Lempas (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the effects of the Free Nutritious Meal Program (MBG) and student well-being on students' learning outcomes, as well as to examine the mediating role of learning motivation. A quantitative approach employing Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze data collected through a structured questionnaire. The measurement model evaluation (outer model) showed that all reflective indicators satisfied the criteria for convergent validity, with outer loadings exceeding 0.70, and demonstrated adequate discriminant validity based on the Fornell–Larcker criterion. The structural model evaluation (inner model) yielded adjusted R² values of 0.290 for learning motivation, indicating moderate explanatory power, and 0.764 for learning outcomes, indicating substantial explanatory power. The direct effect analysis revealed that the MBG Program had positive and significant effects on both learning motivation (β = 0.337, p < 0.05) and learning outcomes (β = 0.227, p < 0.05). Likewise, student well-being positively and significantly influenced learning motivation (β = 0.136, p < 0.05) and learning outcomes (β = 0.692, p < 0.05). Mediation analysis further indicated that learning motivation significantly mediated the relationships between the MBG Program and learning outcomes, as well as between student well-being and learning outcomes. These findings suggest that nutritional support through the MBG Program and students' psychosocial well-being jointly enhance learning motivation, which subsequently contributes to improved learning outcomes.